Pharmacokinetics of prolonged‐release tacrolimus and implications for use in solid organ transplant recipients. Issue 8 (18th June 2016) - Tanzi, Maria G.; Undre, Nasrullah; Keirns, James; Fitzsimmons, William E.; Brown, Malcolm; First, M. Roy
Abstract: Prolonged‐release tacrolimus was developed as a once‐daily formulation with ethylcellulose as the excipient, resulting in slower release and reduction in peak concentration ( C max ) for a given dose compared with immediate‐release tacrolimus, which is administered twice daily. This manuscript reviews pharmacokinetic information on prolonged‐release tacrolimus in healthy subjects, in transplant recipients converted from immediate‐release tacrolimus, and in de novo kidney and liver transplant recipients. As with the immediate‐release formulation, prolonged‐release tacrolimus shows a strong correlation between trough concentration ( C min ) and area under the 24‐hour time–concentration curve (AUC24 ), indicating that trough whole blood concentrations provide an accurate measure of drug exposure. We present the pharmacokinetic similarities and differences between the two formulations, so that prescribing physicians will have a better understanding of therapeutic drug monitoring in patients receiving prolonged‐release tacrolimus.